HPV-related oropharyngeal cancer early detection in gay and bisexual men is an “orphan” practice: A qualitative analysis among healthcare providers - Zoschke, I. Niles; Bennis, Sarah L.; Wilkerson, J. Michael; Stull, Cynthia L.; Nyitray, Alan G.; Khariwala, Samir S.; Nichols, C. Mark; Rosser, B. R. Simon; Flash, Charlene; Ross, Michael W. (Frontiers in Public Health, 2023)
Introduction: Among US men, oropharyngeal cancer (cancer of the back of the mouth and throat) is the 8th most common cancer. If detected early, human papillomavirus (HPV)-16-associated oropharyngeal cancer has a high five-year survival rate. Risk factors such as high numbers of oral sex partners, disparities in smoking and drinking, and low rates of HPV vaccination may put gay and bisexual men at even higher risk for oropharyngeal cancer. Methods: We recruited 21 healthcare providers in Minneapolis-St. Paul, Minnesota and Houston, Texas to participate in semi-structured interviews. Nurses, physician assistants, dental hygienists, and dentists were asked about their clinical experiences serving gay and bisexual men and opinions on potential interventions for the early detection of oropharyngeal cancer. Results: Providers typically did not tailor health screenings and examinations for gay and bisexual men. Participants lacked confidence in their ability to effectively implement routine screening for oropharyngeal cancer. The extent to which oropharyngeal cancer screening was incorporated into clinical practice varied by specialty, and practices necessary to detect it were scattered across clinical environments. HIV- and LGBTQ-focused healthcare providers were more aware of HPV-associated oropharyngeal cancer in gay and bisexual men, and appeared readier to act and lead on this issue. Discussion Further studies should (1) evaluate protocols for oropharyngeal cancer detection; (2) identify and assess the acceptability of screening in the community; and (3) study how to best close gaps in health services for gay and bisexual men which might contribute to low early detection rates of oropharyngeal cancer.